Phase-field modeling of nanostructural evolution in physical vapor deposited phase-separating ternary alloy films. (1st December 2022) - Raghavan, Rahul; Wu, Peichen; Ankit, Kumar
Abstract: Self-assembly by spinodal decomposition is known to be a viable route for synthesizing nanoscaled interfaces in a variety of materials, including metamaterials. In order to tune the response of these specialized materials to external stimuli, knowledge of processing-nanostructure correlations is required. Such an understanding is more challenging to obtain purely by experimental means due to complexity of multicomponent atomic diffusion mechanisms that govern the nanostructural self-assembly. In this work, we introduce a phase-field modeling approach which is capable of simulating the nanostructural evolution in ternary alloy films that are typically synthesized using physical vapor deposition. Based on an extensive parametric study, we analyze the role of the deposition rate and alloy composition on the nanostructural self-assembly in ternary alloy films. The simulated nanostructures are categorized on the basis of nanostructured morphology and mapped over a compositional space to correlate the processing conditions with the film nanostructures. The morphology maps reveal that while deposition rate governs the nanostructural evolution at around equi-molar compositions, the impact of composition on nanostructuring is more pronounced when the atomic ratios of alloying elements are skewed.